Ronald Dworkin - Guest, Stephen (Jurists-- profiles in legal theory., 2013)
Ronald Dworkin is widely accepted as the most important and most controversial Anglo-American jurist of the past forty years. And this same-named volume on his work has become a minor classic in the field, offering the most complete analysis and integration of Dworkin's work to date. This third edition offers a substantial revision of earlier texts and, most importantly, incorporates discussion of Dworkin's recent masterwork Justice for Hedgehogs. Accessibly written for a wide readership, this book captures the complexity and depth of thought of Ronald Dworkin. Displaying a.